MCCC’s Youtube Content Production Management for Covid-19 Education - Fajar Junaedi; Filosa Gita Sukmono; Alisya Chantika Salsabila (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
Muhammadiyah Covid-19 Command Center (MCCC) is an institution established by the Muhammadiyah Central Board to become the center for handling the Covid-19 pandemic. This institution has effectively become a government collaborator in dealing with the pandemic. MCCC conducts health promotion by utilizing various media, including Youtube. This study found that MCCC has a professional standard in producing Youtube content. MCCC always conducts research before the production process. The research is conducted to determine the needs of the community. In the distribution process, MCCC tries to build interaction with the audience. Interaction is an important aspect of increasing engagement. In the end, this involvement is part of the process so that the public understands Covid-19.